Techniques in numerical differentiation of experimentally noisy data - Lopes, H. (2011)
A comparison of different methodologies for spatial differentiation of experimental noisy data is presented. The transient displacement fields resulting from bending wave propagation on aluminum plate were measured with pulse TV-holography. A new method to perform the numerical spatial differentiation and a strategy for dealing with the border problem are presented. The method here presented results for the third order derivative and showed to be superior to the other methods tested. A good agreement between the new method and the Finite Elements Method was achieved.